CURRENT STATE OF THE UKRAINIAN MARKET OF ELECTRONIC PAYMENT SYSTEMS - ZATONATSKA, Tetiana; VOLVACH, Olena (Scientific journal «World of Finance», 2021)
Introduction. Today, almost the only industry in the country that Ukraine can really be proud of and which is considered one of the most technologically advanced in the world is the development of card technologies, payment technologies and card infrastructure. The purpose of the article is to analyze the current state of electronic payment systems in Ukraine and highlight development trends. Results. The modern fintech directions in Ukraine are analyzed and examples of the impact of COVID-19 on the market of electronic payment systems for the last period are given. A number of trends are highlighted for further research in the field of electronic payment systems, which are now quite promising. Perspectives. Given the significant increase in non-cash payments, the problem of developing financial technologies and spreading awareness among the population has become especially urgent. It is necessary to improve not only the financial technologies themselves, but also the ways of providing them to clients and promoting modern financial technologies. Electronic payment systems can still be considered one of the most promising areas for future research.